Maximizing Overall Equipment Effectiveness in a Food Processing Industry: A Case Study - , Christopher Chukwutoo Ihueze, Chukwuebuka Martinjoe U-Dominic (Archives of Current Research International, 2018)
In this study, TPM strategies were deployed to improve the production performance of a manufacturing facility. The OEE quantitative metric has been followed here to solve the underlying problem of reducing the frequency of machine failures and improving its operational efficiency. The results from the study show that the TPM implementation on the packaging machine has increased its OEE value from 48% to 74%, availability factor was raised by 19%; from 70% to 89%, the performance factor experienced an increase too, from the initial value of 70% to 84%, the reliability of the packaging machine increased from 38.91 hr. to 71.83 hr., and the downtime hour on the packaging machine drastically reduced from 834hr to 446 hr., which is about 46.52% hour reduction. The study further reveals that focused TPM implementation over a reasonable period of time can impressively enhance manufacturing performance.